THE USE OF DIGITAL TECHNOLOGIES FOR IMPLEMENTING AN INCLUSIVE APPROACH IN FOREIGN LANGUAGE EDUCATION - ALIMOVA, Kamola Tursunovna (The Lingua Spectrum, 2025)
In the context of the digital transformation of education, digital technologies play a crucial role in supporting the implementation of inclusive educational practices. Contemporary foreign language classrooms are characterized by increasing learner diversity, including differences in linguistic backgrounds, cognitive styles, learning paces, and individual educational needs. This diversity necessitates the adoption of flexible, learner-centered instructional models that ensure equitable access to learning opportunities. The present article examines the potential of digital technologies to facilitate an inclusive approach in foreign language education. It explores key pedagogical functions of digital tools, including differentiation, personalization, accessibility, and learner engagement. Special attention is given to the evolving role of the foreign language teacher as a designer of inclusive digital learning environments. The study concludes that the effective integration of digital technologies significantly enhances the inclusivity and effectiveness of foreign language instruction.